PROMECOPS CLAVIGER HUSTACHE (COLEOPTERA: CURCULIONIDAE). ASPECTOS BIOLÓGICOS Y DAÑOS AL CULTIVO DE LA SOJA EN TUCUMÁN, R. ARGENTINA - Lázaro, H. O.; Nasca, A. J.; Cruz, D. (Acta Entomológica Chilena, 2022)
The most significant aspects of the life cycle of Promecops claviger Hustache (Coleóptera: Curculionidae) that could be used for the management of this pest, are treated here. Weekly samples were taken in soybean fields during 1993/94 and 1994/95 growing seasons in order to assess adult populations. Soil samples were also taken for larvae and pupae. The adults feed on seedlings since soybean emergence. High populations sometimes occur during the vegetative stage. Larvae feed on nodules affecting them up to 1%. Plants are not damaged when environmental conditions are favorable for their development